ปัจจัยที่มีผลต่อความน่าจะเป็นในการเกิดวิกฤตค่าเงินของประเทศเวียดนาม: Factors Affecting the Likelihood of Vietnam Currency Crisis - Silaket, Ploypailin (Asian Health, Science and Technology Reports, 2011)
This research examined the relationship of various factors affecting the probability of currency crisis in Vietnam from the third quarter of 1995 to the fourth quarter of 2008. Using the analyzing method of Binary Response Model by Probit Model, which is a model used to describe the dependent variable which is the quality variable. Currency crisis in this study is defined on the pressure on foreign exchange which is calculated from the weighted average changes of exchange rate and changes in international reserves. The results show that during the third quarter of 1995 to the fourth quarter of 2008, the currency crisis occurred 4 times including the third and the fourth quarter of 1997 and the first and the second quarter of 1998. This findings reveal that factors influencing the probability of currency crisis in Vietnam are the expansion of domestic credit, the proportions of international reserves to short-term foreign debt, the unemployment rate, government budget deficits, foreign exchange rates and the trade balance.